Validação do analisador hematológico automático BC-2800 VET® para realização de hemogramas de muares - Miranda, Gislaine Matias Dantas [UNESP] (2014)
In this study the values of complete blood counts performed in 30 mules aged 4 and 8, obtained by using an automated hematology analyzer and the manual blood counts were compared. The results showed that the correlation between the two methods were considered good since the bias (mean difference) was small, and the confidence intervals of 95 % for the bias showed up narrow and only one outlier was observed for erythrocytes, monocytes and granulocytes (no value fell outside the limits of agreement [bias ± 2 standard deviations]). There was no significant difference in the values of erythrocytes, hemoglobin, leukocytes and granulocytes. The average values obtained from monocytes by an automatic cell counter were significantly higher than those obtained by the manual method. The results also showed a positive bias for hematocrit and no bias was detected in erythrocytes, hemoglobin, leukocytes, granulocytes and lymphocytes. Good agreement between the results obtained by the two methods for erythrocytes, hemoglobin, leukocytes, granulocytes, lymphocytes and monocytes was observed in this age group. Can the automated hematology analyzer BC-2800Vet® be used to perform complete blood counts in mules